Цирк в шкатулке - Сабитова Дина (Сказка "Самоката", 2011)
Экземпляры: ДБ (20120426) / Инвентарный номер: 40655z1zzzzz / Цена: 225.00 / Сис.шифр: 84(2) / Авт.знак: С 12 / ГРНТИ: 17.82.93 / ББК: 84(2=Рус)